Concept of Aircraft Flight Safety Management Using Artificial Intelligence - Ismayilov, I.M. (Herald of Azerbaijan Engineering Academy, 2024)
The article proposes a new concept of building an intelligent aircraft control system, which increases the functionality of the system for its adaptation to the controlled object. Enhanced adaptive system functionality is knowledge-based to help pilots perform important and safety-critical tasks on modern aircraft. The implementation of the proposed system is based on the pilot’s situational awareness of the flight progress in real time, which allows avoiding errors and maintaining enhanced synergy between human and avionics systems. These synergies provide significant improvements in overall flight control performance and safety. Appropriate mathematical models are introduced to assess the mental load associated with each piloting task and assess the pilot’s cognitive abilities and condition.